Studi evaluasi Pencahayaan Alami Pada Gedung Kuliah Bersama Iii Universitas Muhammadiyah Malang - Gw, Ode Rapija; ., Beta Suryo Kusumo (Media Teknik Sipil, 2011)
In Gedung Kuliah Bersama (GKB) III at University Muhammadiyah of Malang, at the first floor with a low-level of illumination should be used for audio-visual rooms or meeting, or it’s not used to read, write a long time (often), and for a thorough job, so it does not require a high level of illumination, because the majority of rooms on the first floor level of 30 lux illumination only and the maximum light level is only about 300 lux at the window. On the second floor with office functions majors and computer labs are appropriate to the level of illumination most of the rooms reached 200 lux, at the window level to 500 lux maximum lighting. Lecture room on 3 and 4 floors have a very high level of illumination, on the third floor reached 120-240 lux in the most of the rooms and around the window to 1200 lux, the uneven illumination very disturbing visual comfort of user room. On the fourth floor most of the rooms have lighting levels of 200-400 lux and 1800 lux maximum reached around the windows.Key Words: Lighting levels or level of illumination, GKB ( Gedung Kuliah Bersama )